Immediate Surroundings as Inspiration: A Semiotic Analysis of Religious Discourse in Norsiah Gapar’s Pengabdian - Najib Noorashid (Asiatic: IIUM Journal of English Language and Literature, 2023)
This paper analyses semiotic elements in Pengabdian, a Malay novel published in 1987 and written by the 2009 SEA award winning Bruneian writer, Norsiah Gapar. Three main themes of semiotics in relation to Islamic principles and values are highlighted in Pengabdian: submission to God, attitudes towards worldly affairs, and the issue of rights and possessions in Islam. Besides the inclusion of explicit sermonic discourse in the novel, semiotic elements are foregrounded to support the edification of Islam to the readers. Following the co-existence of semiotic symbols and sermonic discourse, which is in line with the Islamic requisite of Amar Ma’ruf wa Nahi anil Munkar (enjoining good and forbidding wrong), this essay raises the potential of Pengabdian as a piece of Islamic literature. It offers readers a new way to appreciate Pengabdian from a linguistic-literary perspective, as it also suggests the possibility of undertaking further studies on this acclaimed novel.